Grain Boundaries Control Lithiation of Solid Solution Substrates in Lithium Metal Batteries - Leonardo Shoji Aota; Chanwon Jung; Siyuan Zhang; Ömer K. Büyükuslu; Aparna Saksena; Ezgi Hatipoglu; Poonam Yadav; Mahander Pratap Singh; Xinren Chen; Eric Woods; Christina Scheu; Se‐Ho Kim; et al. (Advanced Science)
Abstract The development of sustainable transportation and communication systems requires an increase in both energy density and capacity retention of Li‐batteries. Using substrates forming a solid solution with body‐centered cubic Li enhances the cycle stability of anode‐less batteries. However, it remains unclear how the substrate microstructure affects the lithiation behavior. Here, a correlative, near‐atomic scale probing approach is deployed through combined ion‐ and electron‐microscopy to examine the distribution of Li in Li‐Ag diffusion couples as model system mimicking high current densities. It is revealed that Li regions with over 93.8% at.% nucleate within Ag at random high‐angle grain boundaries, whereas grain interiors are not lithiated. The role of kinetics and mechanical constraint from the microstructure over equilibrium thermodynamics in dictating the lithiation process is evidenced. The findings suggest that grain size and grain boundary character are critical to enhance the electrochemical performance of interlayers/electrodes, particularly for improving lithiation kinetics and hence reducing dendrite formation.